Analysis of Drug and Health Resource Use Before and After COVID-19 Lockdown in a Population Undergoing Treatment for Depression or Anxiety - Lear-Claveras, Ana; Clavería, Ana; Couso-Viana, Sabela; Nabbe, Patrice; Oliván-Blázquez, Bárbara (Frontiers in Psychology, 2022)
Introduction: The arrival of the pandemic modified the functions of Primary Care teams, which were forced to focus their resources on the diagnosis and treatment of infected patients. The disrupted healthcare of individuals with pre-existing mental disorders (depression or anxiety), as well as the psychological decompensation resulting from the lockdown caused by the COVID-19 pandemic, may have modified the use of drugs and health resources by these patients. Materials and methods: Real world data observational study of 110,694 individuals aged ˃16 years suffering from active or undergoing treatment for depression or anxiety according to the electronic medical records of the Aragon Regional Health Service (Spain). Pharmacological variables (daily dose per inhabitant (DHD) dispensed by pharmacies of: anxiolytics, hypnotics/sedatives, and antidepressants) and variables related to the use of healthcare resources (number of primary and specialized healthcare visits) were considered. Student’s T-tests for paired samples were performed to analyze differences between periods. Results: The use of benzodiazepines increased as compared to its use over the 6 months prior to the lockdown. In contrast, the consumption of antidepressants was found to decrease. The use of health resources continued to be below pre-pandemic levels, 6 months post-lockdown end. Conclusions: Changes in the use of health resources could have a negative impact on the parameters of these diseases. The increase in drug use, especially benzodiazepines, may suggest a worsening of the symptoms during the lockdown and in the subsequent months. It is a worrying sign, which points to the growth of this public health problem and the need for its prevention.